Higher education during the pandemic. An overview of the higher education system in Uzbekistan - Cytlak, Izabela; Mamadaminova, Nigora (Kultura-Społeczeństwo-Edukacja, 2021)
The article focuses on the development of the education system in Uzbekistan after the country gained independence. It highlights the obstacles to the development of the education system and changes during the pandemic, particularly in the sphere of higher education. The purpose of this research is to provide an overview of the steps in the development of education within the state. It will also evaluate the present condition of higher education during the pandemic. The conclusion states the findings and recommendations for further development.